2022
DOI: 10.1002/acm2.13512
|View full text |Cite
|
Sign up to set email alerts
|

Small spot size versus large spot size: Effect on plan quality for lung cancer in pencil beam scanning proton therapy

Abstract: The purpose of the current study was to evaluate the impact of spot size on the interplay effect, plan robustness, and dose to the organs at risk for lung cancer plans in pencil beam scanning (PBS) proton therapy Methods: The current retrospective study included 13 lung cancer patients. For each patient, small spot (∼3 mm) plans and large spot (∼8 mm) plans were generated. The Monte Carlo algorithm was used for both robust plan optimization and final dose calculations. Each plan was normalized, such that 99% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…First, planning strategies (e.g., robust optimization with setup and range uncertainties, optimization on average intensity projection CTs (AIP-CTs) vs. multiple 4DCTs) utilized in these studies were different. A robust optimization technique was applied in the studies by Liu et al 19 and Rana et al, 20 while it was not applied by Grassberger et al 17 and this present study. The use of robust optimization, which includes setup and range uncertainties, inevitably generates plans that are more robust against the interplay effect.…”
Section: D Robust Optimization and Machine Characteristicsmentioning
confidence: 95%
See 4 more Smart Citations
“…First, planning strategies (e.g., robust optimization with setup and range uncertainties, optimization on average intensity projection CTs (AIP-CTs) vs. multiple 4DCTs) utilized in these studies were different. A robust optimization technique was applied in the studies by Liu et al 19 and Rana et al, 20 while it was not applied by Grassberger et al 17 and this present study. The use of robust optimization, which includes setup and range uncertainties, inevitably generates plans that are more robust against the interplay effect.…”
Section: D Robust Optimization and Machine Characteristicsmentioning
confidence: 95%
“…In the other rescanning study, 18 Grassberger et al showed that mitigation of interplay effect for tumor motion amplitudes up to 20 mm (seen in 4/5 patients in their study) required two repaintings for large,and six for small,spot machines.Liu et al 19 reported comparable interplay effect between large and small spot machines, where similar target dose coverage (D 95% ) was observed. In the study by Rana et al, 20 they showed that large spot plans were more robust against the interplay effect in the absence of repainting, with target coverage higher by 1.5% compared to small spot plans. Following VR, the interplay target coverage in small spot plans was found to be comparable to that of the large spot plans.…”
Section: Impact Of Spot Sizes On the Interplay Effectmentioning
confidence: 98%
See 3 more Smart Citations